Comparing supraspinatus to acromion proximity and kinematics of the shoulder and thorax between manual wheelchair propulsion styles: A pilot study. (April 2020) - Madansingh, Stefan I.; Fortune, Emma; Morrow, Melissa M.; Zhao, Kristin D.; Cloud-Biebl, Beth A.
Abstract: Background: Repetitive glenohumeral joint movement during manual wheelchair propulsion has been associated with shoulder pain in individuals with spinal cord injury. Clinical guidelines for shoulder health maintenance encourage semi-circular over arc propulsion to reduce loading frequency. This study aimed to determine the difference in estimated supraspinatus to acromion compression risk, and shoulder, thorax kinematics between (1) arc and semi-circular propulsion; and (2) self-selected and coached strategies. Methods: Shoulder and thorax kinematics were captured during wheelchair propulsion, noting individually self-selected styles. Participants were then coached to perform the other style(s) of interest, arc and/or semi-circular. CT bone models of the humerus and scapula were animated using glenohumeral kinematics to estimate the minimum distance between the supraspinatus humeral attachment and the acromion. Compression risk was defined as the proportion of each propulsion phase where the minimum distance fell below 5 mm. Comparisons were made between conditions evaluating compression risk, minimum distances and kinematics at events throughout propulsion. Findings: Ten individuals with spinal cord injury (9 male) participated. Arc and semi-circular propulsion did not significantly differ in compression risk or minimum distance across propulsion phases. Self-selected styles yielded lower compression risk and larger proximity values compared to coached styles. Glenohumeral horizontal abduction and thorax flexion differed between arc and semi-circular propulsion. Multiple glenohumeral and humerothoracic differences emerged between self-selected and coached conditions. Interpretation: Supraspinatus compression was observed during both arc and semi-circular propulsion, suggesting risk may be unavoidable in this task. Self-selected styles yield less risk, likely related to coached style unfamiliarity. Highlights: Compression risk between the supraspinatus and acromion occurs during wheelchair propulsion. No differences in compression risk were found between arc and semi-circular propulsion. Self-selected propulsion styles showed less compression risk than coached styles. Results support adoption of semi-circular propulsion style to maintain shoulder health.